Strategi Permainan Estafet untuk Meningkatkan Kreativitas Siswa di SD/MI - Fhitriansyah, Iqbal; Anzani, Sindy; Nasution, Nadilla Indriani; Suyono, Suyono (Lembaga Yasin AlSys, 2024)
Creativity is one of the important aspects in developing student potential at the elementary/middle school level. For this reason, a learning method is needed that can stimulate and develop student creativity, one of which is through relay games. This study aims to explore the strategy of relay games as an effort to increase students' creativity in SD/MI. The method used is a field experiment involving 18 students divided into three groups. Data was collected through observation, creativity tests, and interviews. The results showed that the group that participated in the relay games experienced a significant increase in aspects of creativity, such as the ability to think innovatively, generate new ideas, and work in a team. Based on these results, it can be concluded that relay games are effective in increasing students' creativity in elementary school. Therefore, the relay game strategy is recommended to be applied.